Self-administration of gender-affirming hormones: a systematic review of effectiveness, cost, and values and preferences of end-users and health workers. Issue 3 (1st January 2022) - Kennedy, Caitlin E.; Yeh, Ping Teresa; Byrne, Jack; van der Merwe, L. Leigh Ann; Ferguson, Laura; Poteat, Tonia; Narasimhan, Manjulaa
Abstract: Self-administration of quality gender-affirming hormones is one approach to expanding access to hormone therapy for individuals seeking secondary sex characteristics more aligned with their gender identity or expression and can be empowering when provided within safe, supportive health systems. To inform World Health Organization guidelines on self-care interventions, we systematically reviewed the evidence for self-administration compared to health worker-administration of gender-affirming hormones. We conducted a comprehensive search for peer-reviewed articles and conference abstracts that addressed effectiveness, values and preferences, and cost considerations. Data were extracted in duplicate using standardised forms. Of 3792 unique references, five values and preferences articles were included; no studies met the criteria for the effectiveness or cost reviews. All values and preferences studies focused on self-administration of unprescribed hormones, not prescribed hormones within a supportive health system. Four studies from the U.S. ( N  = 2), Brazil ( N  = 1), and the U.K. ( N  = 1) found that individuals seeking gender-affirming hormone therapy may self-manage due to challenges finding knowledgeable and non-stigmatising health workers, lack of access to appropriate services, exclusion, and discomfort with health workers, cost, and desire for a faster transition. One study from Thailand found health worker perspectives were shaped by restrictive legislation, few transgender-specific services or guidelines, inappropriate communication with health workers, and medical knowledge gaps. There is limited literature on self-administration of gender-affirming hormone therapy. Principles of gender equality and human rights in the delivery of quality gender-affirming hormones are critical to expand access to this important intervention and reduce discrimination based on gender identity.